A Longitudinal Study on Online Sexual Engagement, Victimization, and Psychosocial Well-Being - Reer, Felix; Wendt, Ruth; Quandt, Thorsten (Frontiers in Psychology, 2021)
Several cross-sectional studies have shown that online sexual engagement (OSE) in the form of sexting or sexy self-presentation on social media is associated with an increased risk of experiencing negative consequences, such as online sexual victimization (OSV) or lower levels of psychosocial well-being. However, representative and longitudinal studies are scarce. The current study follows three research goals: (1) examining the prevalence of OSE and OSV among a random-quota sample of 1,019 German Internet users aged 14–64 years, (2) examining gender and age-related differences in OSE and OSV, and (3) examining the longitudinal relationships between OSE, OSV, and psychosocial well-being over a period of 1 year. Our results indicate that OSE and OSV are relatively widespread: 17.7% of the participants had already experienced OSV, 25.3% indicated that they had presented themselves online in a sexualized manner at least once in the past 2 months, and 22.7% showed a certain willingness to engage in sexting. We found higher rates among the younger participants. However, to a certain degree, older individuals were also affected. Male participants showed higher sexting willingness and more often presented themselves in a sexualized manner than females, whereas only small differences related to OSV were found. Concerning relationships with psychosocial well-being, our cross-sectional results showed that OSE, OSV, and mental problems are intercorrelated. Furthermore, we detected a significant long-term relationship between higher sexting willingness at time 1 and more victimization experienced 1 year later, whereas no significant longitudinal associations with lower levels of psychosocial well-being were identified.